Upregulated ribosome pathway plays a key role in HDAC4, improving the survival rate and biofunction of chondrocytes - Li Guo; Hua Guo; Yuanyu Zhang; Zhi Chen; Jian Sun; Gaige Wu; Yunfei Wang; Yang Zhang; Xiaochun Wei; Pengcui Li (Bone & Joint Research, 2023)
Aims: To explore the novel molecular mechanisms of histone deacetylase 4 (HDAC4) in chondrocytes via RNA sequencing (RNA-seq) analysis. Methods: Empty adenovirus (EP) and a HDAC4 overexpression adenovirus were transfected into cultured human chondrocytes. The cell survival rate was examined by real-time cell analysis (RTCA) and EdU and flow cytometry assays. Cell biofunction was detected by Western blotting. The expression profiles of messenger RNAs (mRNAs) in the EP and HDAC4 transfection groups were assessed using whole-transcriptome sequencing (RNA-seq). Volcano plot, Gene Ontology, and pathway analyses were performed to identify differentially expressed genes (DEGs). For verification of the results, the A289E/S246/467/632 A sites of HDAC4 were mutated to enhance the function of HDAC4 by increasing HDAC4 expression in the nucleus. RNA-seq was performed to identify the molecular mechanism of HDAC4 in chondrocytes. Finally, the top ten DEGs associated with ribosomes were verified by quantitative polymerase chain reaction (QPCR) in chondrocytes, and the top gene was verified both in vitro and in vivo. Results: HDAC4 markedly improved the survival rate and biofunction of chondrocytes. RNA-seq analysis of the EP and HDAC4 groups showed that HDAC4 induced 2,668 significant gene expression changes in chondrocytes (1,483 genes upregulated and 1,185 genes downregulated, p < 0.05), and ribosomes exhibited especially large increases. The results were confirmed by RNA-seq of the EP versus mutated HDAC4 groups and the validations in vitro and in vivo. Conclusion: The enhanced ribosome pathway plays a key role in the mechanism by which HDAC4 improves the survival rate and biofunction of chondrocytes. Cite this article: Bone Joint Res 2023;12(7):433–446.